2022
DOI: 10.1021/jacs.2c00521
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthetic Landscape of Triceptides Reveals Radical SAM Enzymes That Catalyze Cyclophane Formation on Tyr- and His-Containing Motifs

Abstract: Peptide-derived cyclophanes inhabit a unique niche in the chemical space of macrocyclic peptides with several examples of pharmaceutical importance. Although both synthetic and biocatalytic methods are available for constructing these macrocycles, versatile (bio)­catalysts able to incorporate a variety of amino acids that compose the macrocycle would be useful for the creation of diverse peptide cyclophanes. In this report, we synergized the use of bioinformatic tools to map the biosynthetic landscape of radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 58 publications
(130 reference statements)
2
62
0
Order By: Relevance
“…More recently, manual inspection of clusters from an EFI-EST-based network of RaS enzymes led to the discovery of an enzyme that catalyzes the repeated formation of cyclopropylglycine from valine, a new reaction for RaS enzymes . Additionally, an SSN approach has been used to map the biosynthetic landscape of cyclophane-forming RaS enzymes, revealing new cyclophane macrocycles . To make these sorts of analyses easier, RadicalSAM.org was created as a web-based tool for the analysis of SSNs for the entire RaS family …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, manual inspection of clusters from an EFI-EST-based network of RaS enzymes led to the discovery of an enzyme that catalyzes the repeated formation of cyclopropylglycine from valine, a new reaction for RaS enzymes . Additionally, an SSN approach has been used to map the biosynthetic landscape of cyclophane-forming RaS enzymes, revealing new cyclophane macrocycles . To make these sorts of analyses easier, RadicalSAM.org was created as a web-based tool for the analysis of SSNs for the entire RaS family …”
Section: Resultsmentioning
confidence: 99%
“…35 Additionally, an SSN approach has been used to map the biosynthetic landscape of cyclophane-forming RaS enzymes, revealing new cyclophane macrocycles. 36 To make these sorts of analyses easier, RadicalSAM.org was created as a web-based tool for the analysis of SSNs for the entire RaS family. 34 We set out to develop a bioinformatics platform that could benefit from the use of SSNs but would also include computational filtering steps to limit the amount of manual analysis required.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Broad substrate selectivity on other aliphatic residues further increases the enzyme-catalyzed chemical space of cyclic peptides. While this manuscript was under preparation, Brandon I. Morinaka and coworkers reported the HaaA precursor family with the same His-Ala crosslink, which resembles our ScaA family, and the YhhA family with similar conserved residues to the VguA family [31] . Together with our bioinformatic data, these findings suggested that histidine-involved post-translational cyclization is prevalent in bacteria.…”
Section: Discussionmentioning
confidence: 79%
“…Based on the residue-defined modification logic, three families expected to encode new chemical space were prioritized and characterized in this study (Figure 3, Table S29- 31). BlaA family was selected for functional characterization due to two conserved cysteines and two conserved glycine residues in the C-terminal, which may be catalyzed to form two Cys-to-Gly thioether bonds(Figure 3A).…”
Section: Speco-based Mining Reveals the Landscape Of Rsam-catalyzed R...mentioning
confidence: 99%
“…While this manuscript was under preparation, Morinaka and coworkers reported the HaaA and the YhhA families which respectively resembled our ScaA family and VguA family. [33] Phylogenetic analysis of these cyclophane-forming rSAM enzymes revealed that a divergence event may have occurred in the FxS maturase family (TIGR04269) to give rise to ScaB and VguB families (Figure S64).…”
Section: Methodsmentioning
confidence: 99%